An analysis of the Spanish ceramic tile industry research contracts and patents. Issue 5 (4th May 2018) - Gabaldón-Estevan, Daniel; Manjarrés-Henríquez, Liney; Molina-Morales, F. Xavier
ABSTRACT: In this work, we apply a systemic approach to the analysis of a particular geographic territory, the industrial district. We are particularly interested in analysing the interaction between the productive-technological environment and the scientific environment by an examination of research contracts and patents. Our analysis shows that R&D activity in the Spanish ceramic tile District Innovation System was mainly conducted by suppliers. Final producers' innovation efforts were related to non-technological aspects and differentiation.